CAPM - Empirical Evidence from the Indian Stock Market - Anwar, Mobin; Kumar, Sanjay (Indian Journal of Research in Capital Markets, 2018)
The CAPM model does not hold very strong in stock markets as evidenced by recent empirical tests. However, it has become a basis for the development of other models of asset pricing or extension of the same model. The model advocated the efficiency and efficacy of different markets as far as pricing of capital assets is concerned, and it is the price fluctuations which are responsible for capital gains for investors. A large number of tests in asset pricing literatures have been carried out in developed nations. On the other hand, these tests are witnessed to be in dearth in developing nations, and India is not an exception. The emerging markets are more volatile, and this is the reason it is more interesting. The present piece of research attempted to explain the extent to which the CAPM model is able to explain price fluctuations in India. The study used NIFTY 50 companies as a sample. NIFTY 50 companies were also subcategorized by size and value, and the effect of size and value was detected on the return of the asset. It covered a period from April 1, 2009 to March 31, 2016. The CAPM was not found to be robust in explaining the asset returns. CAPM explained the returns more in case of portfolio assets as compared to individual assets, though the degree was very low. Big size firms outperformed the small size firms. Also, the low - value firms outperformed the high-value firms. In a majority of the cases, the market volatility was found in excess to the asset volatility.